Pengaruh Pemberian Rhodamin B Terhadap Struktur Histologis Ginjal Mencit Putih (Mus musculus L.) - Riska Mayori; Netty Marusin; Djong Hon Tjong (Universitas Andalas, 2013)
Rhodamine B is synthetic textile dye that currently still used for food coloring. Thus, it is important to analyse the effect of the substance on health. It was aimed to identify the histological structure changes of the mice kidney caused by Rhodamin B. This research was used experimental method with Completely Randomized Design in factorial pattern consisting of two factors such as dose of (0; 3.5; 7.0 and 14 mg/g body weight) and duration of treatment (0; 7; 14 and 21 days). The result showed that of dose and duration of treatment Rhodamin B have significant effect on the percentages of glomerular damage, and so did the interactions of both factors. Histological analysis showed the presence of narrowing of bowman space in glomerular, hipertrophy, necrosis and serosis of the tubules. The higher dose and the longer duration of treatment of Rhodamin B, the more serious of structural damages of kidney.Keywords : Rhodamin B, kidney, Mus musculus